Exploring factors impacting early childhood health among Aboriginal and Torres Strait Islander families and communities: protocol for a population-based cohort study using data linkage (the 'Defying the Odds' study). Issue 3 (28th March 2018) - McNamara, Bridgette; Gubhaju, Lina; Jorm, Louisa; Preen, David; Jones, Jocelyn; Joshy, Grace; Shepherd, Carrington; McAullay, Daniel; Eades, Sandra
Abstract : Introduction: Empirical evidence on family and community risk and protective factors influencing the comparatively high rates of potentially preventable hospitalisations and deaths among Aboriginal and Torres Strait Islander infants and children is limited. As is evidence on geographical variation in these risks. The 'Defying the Odds' study aims to explore the impact of perinatal outcomes, maternal social and health outcomes and level of culturally secure service availability on the health outcomes of Western Australian (WA) Aboriginal infants and children aged 0–5 years. Methods and analysis: The study combines a retrospective cohort study that uses state-wide linked health and administrative data from 12 data sources for multiple generations within Aboriginal families in WA, with specifically collected survey data from health and social services supporting Aboriginal families in regions of WA. Data sources include perinatal/birth registration, hospital, emergency department, mental health services, drug and alcohol service use, mortality, infectious disease notifications, and child protection and family services. Multilevel regression models will be used to examine the intensity of admissions and presentations, mortality, intensity of long stays and morbidity-free survival (no admissions) for Aboriginal children born in WA in 2000–2013. Relationships between maternal (and grand-maternal) health and social factors and child health outcomes will be quantified. Community-level variation in outcomes for Aboriginal children and factors contributing to this variation will be examined, including the availability of culturally secure services. Online surveys were sent to staff members at relevant services to explore the scope, reach and cultural security of services available to support Aboriginal families across selected regions of WA. Ethics and dissemination: Ethics approvals have been granted for the study. Interpretation and dissemination are guided by the study team's Aboriginal leadership and reference groups. Dissemination will be through direct feedback and reports to health services in the study and via scientific publications and policy recommendations.